2015
DOI: 10.5370/jeet.2015.10.3.719
|View full text |Cite
|
Sign up to set email alerts
|

Field Implementation of Voltage Management System (VMS) into Jeju Power System in Korea

Abstract: -This paper presents the results of field tests on Voltage Management System (VMS) using hybrid voltage control, which utilizes coordinated controls of various reactive power resources such as generators, FACTS and switched shunt devices to regulate the pilot bus voltage in a voltage control area. It also includes the results of performance test on RTDS-based test bed in order to validate the VMS before installing it in Jeju power system. The main purpose of the system is adequately to regulate the reactive po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It is noteworthy that many utilities have recently evaluated their CVR performance through numerous commissions and strategies as well as the technical and economic benefits of peak demand reduction and energy savings [1][2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The Pacific Northwest National Laboratory (PNNL) reported that the CVR on a national level in the U.S. can be extrapolated to be 3.04% reduction in annual energy consumption [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that many utilities have recently evaluated their CVR performance through numerous commissions and strategies as well as the technical and economic benefits of peak demand reduction and energy savings [1][2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The Pacific Northwest National Laboratory (PNNL) reported that the CVR on a national level in the U.S. can be extrapolated to be 3.04% reduction in annual energy consumption [17].…”
Section: Introductionmentioning
confidence: 99%